Discourses on the miraculous in the living environment of the present-day person - Astapov, Sergey (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2024)
The article is devoted to the recognizing of the meaning of discourses on the miraculous in the human life environment. This meaning is to be a sign or trigger for a radical transformation in the semantic sphere of life. The role of miracle as sacred phenomena is recognized as the sign of religious transformation of a personality, and the role of the miraculous, that is, a desecrated miracle, is recognized as an interruption of everyday life, giving an impetus for acquisition of new goals and meanings of human existence. The article argues that an event becomes miraculous not during its occurrence, but rather as a result of a posteriori comprehension and articulation through narrative. Six types of discourses about the miraculous have identified it the article. They present different ways of understanding of the place and role in the human life environment. Theistic discourses, representing the miracle as the manifestation of the sacred, orientate to accept the event as a divine sign, indicating either a personal transformation that has already occurred, or the urgent need for a lifestyle change. Mythological and magical discourses about miracles as manifestations of an alien force are aimed at affirming the idea of the superiority of an agent of miracles over natural processes occurring in the living environment. Esoteric discourses about miracles often mystify unusual occurrence by attributing them to phenomena outside of scientific understanding, but at the same time, they activate the cognitive search of the individual. Fantastic discourses, constructing miracles in fictional environments, not only serve as entertainment, but also stimulate synthesis of variety of sensory-visual representations into holistic images, and sometimes they serve didactic purposes. Aesthetic discourses reveal the beauty of natural and cultural phenomena, creative discourses – the genius of solutions and the embodiment of ideas. Both of them stimulate human projective activity, shifting attention from everyday affairs and the usual course of events towards something beyond ordinary. This explains presence of discourses about miracles in modern culture.